PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERN TERHADAP AKUNTAILITAS KINERJA - Sari, Eka Kartika; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of the use of information technology and internal control to the performance accountability at Dinas Pendapatan dan Pengelolaan Keuangan Kota Surabaya. Based on the type of the research, this research employs quantitative method and the sample collection technique has been done by using purposive sampling. The data collection technique has been done by using survey method, The data analysis and the processing have been done by using multiple linear regressions and the support of SPSS Software (Statically Product and Service Solution). The result of the research shows that the use of information technology has significant influence to the performance accountability with the value of regressions coefficient is 12.324 and the significance value is 0.000 (alpha 0.05). The internal control has significant influence to the performance accountability with the coefficient regressions value is 2.373 and the significance value is 0.026 (alpha 0.05). Meanwhile, the R square value is 0.876 it means that 87.6% of the independent variable in this research can influence the dependent variable.Keywords: The Use of Information Technology, Internal Control, Performance Accountability